"I don´t put people into boxes, but…" A free-listing exercise exploring social categorisation of asylum seekers by professionals in two German reception centres. - Sandra Ziegler; Kayvan Bozorgmehr (PLOS Global Public Health, 2024)
Newly arriving asylum seekers in Germany mostly live in large reception centres, depending on professionals in most aspects of their daily lives. The legal basis for the provision of goods and services allows for discretionary decisions. Given the potential impact of social categorisation on professionals' decisions, and ultimately access to health and social services, we explore the categories used by professionals. We ask of what nature these categorisations are, and weather they align with the public discourse on forced migration. Within an ethnographic study in outpatient clinics of two refugee accommodation centres in Germany, we conducted a modified free-listing with 40 professionals (physicians, nurses, security-personnel, social workers, translators) to explore their categorisation of asylum seekers. Data were qualitatively analysed, and categories were quantitatively mapped using Excel and the Macro "Flame" to show frequencies, ranks, and salience. The four most relevant social categorisations of asylum seekers referred to "demanding and expectant," "polite and friendly" behaviour, "economic refugees," and "integration efforts". In general, sociodemographic variables like gender, age, family status, including countries and regions of origin, were the most significant basis for categorisations (31%), those were often presented combined with other categories. Observations of behaviour and attitudes also influenced categorisations (24%). Professional considerations, e.g., on health, education, adaption or status ranked third (20%). Social categorisation was influenced by public discourses, with evaluations of flight motives, prospects of staying in Germany, and integration potential being thematised in 12% of the categorisations. Professionals therefore might be in danger of being instrumentalised for internal border work. Identifying social categories is important since they structure perception, along their lines deservingness is negotiated, so they potentially influence interaction and decision-making, can trigger empathy and support as well as rejection and discrimination. Larger studies should investigate this further. Free-listing provides a suitable tool for such investigations.